PENGARUH FILTRASI TERHADAP NILAI pH, TDS, KONDUKTANSI DAN SUHU AIR LIMBAH LAUNDRY - Farly Tumimomor; Septiany Palilingan; Meity Pungus (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Laundry wastewater has the potential to pollute the aquatic environment if it is thrown away in large volumes without any prior treatment. The easy and inexpensive laundry wastewater treatment method for household-scale has been carried out through the filtration method using a combination of natural adsorbent as a laundry wastewater filtration media. This study aims to determine the effect of filtration using a combination adsorbents of activated charcoal, zeolites, silica sand, anthracite and ferolite on pH, TDS (Total Dissolved Solid), electrical conductivity and temperature values ​​in laundry wastewater samples. Based on laboratory test results, it was found that after the filtration process, a pH value of 22.2% was decreased, the TDS level was 21.5% and the conductance value was 15.1%, while the temperature value was relatively stable. Statistically, the presence of filtration treatment only gives a significant influence on changes in pH, TDS and conductance values ​​while the relative temperature value does not change.